Water Buffalo Genome Science Comes of Age - Michelizzi, Vanessa N.; Dodson, Michael V.; Pan, Zengxiang; Amaral, M. Elisabete J. [UNESP]; Michal, Jennifer J.; McLean, Derek J.; Womack, James E.; Jiang, Zhihua (Ivyspring Int Publ, 2010)
The water buffalo is vital to the lives of small farmers and to the economy of many countries worldwide. Not only are they draught animals, but they are also a source of meat, horns, skin and particularly the rich and precious milk that may be converted to creams, butter, yogurt and many cheeses. Genome analysis of water buffalo has advanced significantly in recent years. This review focuses on currently available genome resources in water buffalo in terms of cytogenetic characterization, whole genome mapping and next generation sequencing. No doubt, these resources indicate that genome science comes of age in the species and will provide knowledge and technologies to help optimize production potential, reproduction efficiency, product quality, nutritional value and resistance to diseases. As water buffalo and domestic cattle, both members of the Bovidae family, are closely related, the vast amount of cattle genetic/genomic resources might serve as shortcuts for the buffalo community to further advance genome science and biotechnologies in the species.
Keywords: Water buffalo; Genome resources; Cytogenetic; Whole genome mapping; next generation sequencing; Genome biotechnology